2013
DOI: 10.1016/j.mehy.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-X, collagen, and Ehlers–Danlos syndrome: Tenascin-X gene defects can protect against adverse cardiovascular events

Abstract: Long thought to be two separate syndromes, Ehlers-Danlos syndrome hypermobility type (EDS-HT) and benign joint hypermobility syndrome (BJHS) appear on close examination to represent the same syndrome, with virtually identical clinical manifestations. While both EDS-HT and BJHS were long thought to lack the genetic loci of other connective tissue disorders, including all other types of EDS, researchers have discovered a genetic locus that accounts for manifestations of both EDS-HT and BJHS in a small population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…To date, no collagen defects and/or associated mutations have been found in JHS/EDS‐HT. Only in 5‐10% of patients a mutation in TNXB, the gene that codes for tenascin‐X, a glycoprotein in the ECM that is responsible for organization and maintenance of the matrix itself, was linked to an autosomal recessive form of JHS/EDS‐HT . Notably, we have previously reported that GI symptoms are encountered frequently in tenascin‐X‐deficient patients .…”
Section: Discussionmentioning
confidence: 99%
“…To date, no collagen defects and/or associated mutations have been found in JHS/EDS‐HT. Only in 5‐10% of patients a mutation in TNXB, the gene that codes for tenascin‐X, a glycoprotein in the ECM that is responsible for organization and maintenance of the matrix itself, was linked to an autosomal recessive form of JHS/EDS‐HT . Notably, we have previously reported that GI symptoms are encountered frequently in tenascin‐X‐deficient patients .…”
Section: Discussionmentioning
confidence: 99%
“…An inherited alteration of ECM could, therefore, hold a role in an abnormal synaptic functioning and in the development of neuropsychiatric disorders linked to other extra‐neurologic manifestations [Dityatev et al, ]. In this regard, it is noteworthy that TNXB (6p21.33) encoding for tenascin‐XB, an ECM glycoprotein involved in the organization and maintenance of the connective tissue structure [Petersen and Douglas, ], has been linked to both autosomal dominant and autosomal recessive EDS [Burch et al, ; Schalkwijk et al, ; Zweers et al, , ; Voermans et al, ]. Notably, the locus containing TNXB has been also associated with schizophrenia [Wei and Hemmings, ; Tochigi et al, ; Ripke et al, ], while mice lacking the gene for tenascin‐XB show increased anxiety [Kawakami and Matsumoto, ].…”
Section: Discussionmentioning
confidence: 99%
“…Petersen and Douglas 123 ) hypothesized that a deficiency in or haploinsufficiency of TNX reduced risk factors for adverse cardiovascular events by the laxity of arterial stiffness. However, this hypothesis does not appear to be supported by existing data.…”
Section: Tnxmentioning
confidence: 99%